JA Clinical Reports - Hirota, Kazuyoshi
JA Clinical Reports is a companion journal to the Journal of Anesthesia (JA), the official journal of the Japanese Society of Anesthesiologists (JSA). This journal is an open access, peer-reviewed, online journal related to clinical anesthesia practices such as anesthesia management, pain management and intensive care. Case reports are very important articles from the viewpoint of education and the cultivation of scientific thinking in the field of anesthesia. However, submissions of anesthesia research and clinical reports from Japan are notably decreasing in major anesthesia journals. Therefore, the JSA has decided to launch a new journal, JA Clinical Reports, to encourage JSA members, particularly junior Japanese anesthesiologists, to publish papers in English language.